Thermoelectric property features of PbTe monocrystalline and polycrystalline films - Freik, D.M.; Zapukhlyak, R.I.; Lopjanka, M.A.; Mateik, G.D.; Mikhajlonka, R.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The equations of a regression were obtained by methods of mathematical planning of manyfactors experiments. These equations determine a dependence of thermoelectric parameters of PbTe thin films prepared by hot wall the method from technological factors: temperatures of evaporation, walls of the chamber and deposition. PbTe thin films were layed sieged on pins (111) of BaF₂ monocrystals and on amorphous polyamid fillet PM-1. The ranges of change of these thermoelectic parametres were determined. They respond to the best values of thermoelectric parameters of PbTe thin films. It is shown that the value of thermoelectric parameters of PbTe thin polycrystalline films is bigger in
several times then the monocrystalline ones.